Accumulation of polyunsaturated fatty acid‐derived metabolites in the sarcopenic muscle of aging mice. Issue 4 (22nd February 2023) - Kadoguchi, Tomoyasu; Shimada, Kazunori; Fukui, Naoshi; Tanaka, Nobuho; Tsuno, Hirotaka; Shiozawa, Tomoyuki; Fukao, Kosuke; Nishitani‐Yokoyama, Miho; Isoda, Kikuo; Matsushita, Satoshi; Yokoyama, Norihiko; Daida, Hiroyuki
Abstract : Aim: Although it is known that advanced age alters skeletal muscle lipid metabolism, the role(s) of polyunsaturated fatty acid‐derived metabolites (mostly eicosanoids and docosanoids) in sarcopenia are not clear. We therefore examined the changes in the metabolites of arachidonic acid, eicosapentaenoic acid and docosahexaenoic acid in the sarcopenic muscle of aged mice. Methods: We used 6‐ and 24‐month‐old male C57BL/6J mice as healthy and sarcopenic muscle models, respectively. Skeletal muscles were removed from the lower limb and subjected to a liquid chromatography–tandem mass spectrometry analysis. Results: The liquid chromatography–tandem mass spectrometry analysis detected distinct changes of metabolites in the muscles of the aged mice. Of the 63 metabolites identified, nine were significantly higher in the sarcopenic muscle of aged mice compared with the healthy muscle of young mice. In particular, prostaglandin E2, prostaglandin F2a, thromboxane B2, 5‐hydroxyeicosatetraenoic acid, and 15‐oxo‐eicosatetraenoic acid (arachidonic acid‐derived metabolites), 12‐hydroxy‐eicosapentaenoic acid and 14, 15‐epoxy‐eicosatetraenoic acid (eicosapentaenoic acid‐derived metabolites) and 10‐hydroxydocosa‐hexaenoic acid and 14‐hydroxyoctadeca‐pentaenoic acid (docosahexaenoic acid‐derived metabolites) were significantly higher in aged tissue compared with young tissue (all P < 0.05). Conclusions: We observed the accumulation of metabolites in the sarcopenic muscle of aged mice. Our results may provide new insights into the pathogenesis and progression of aging‐ or disease‐related sarcopenia. Geriatr Gerontol Int 2023; 23: 297–303 .